2016
DOI: 10.1371/journal.pone.0158948
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Retinal and Choroidal Measurements in Chinese School-Age Children with Cirrus-HD Optical Coherence Tomography

Abstract: PurposeTo evaluate retinal thickness (RT), retinal volume (RV) and choroidal thickness (ChT) in Chinese children using Cirrus-HD optical coherence tomography (OCT), and assess their associations with spherical equivalent (SE), age and gender.MethodsThis was a prospective study that recruited 193 healthy Chinese children (193 eyes) with no ophthalmic disease history between December 2012 and December 2013. RT and RV were acquired using OCT. Subfoveal ChT (SFCT) and ChT1-mm and 2-mm temporal, nasal, superior and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 32 publications
4
24
0
Order By: Relevance
“…The SFCT of Chinese children aged from 8 to 11 years was 262.00 ± 40.57 µ m in the mild myopia group and 236.00 ± 55.08 µ m in the moderate myopia group. The mean SFCT of Chinese children had been reported ranging from 245 ± 66 μ m to 302 ± 63 μ m depending on different age and refractive error range [ 10 12 , 23 ]. The SFCT of the mild myopia group in this research was consistent with a previous study of Chinese children, but SFCT of the moderate myopia group was thinner than that in the study [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The SFCT of Chinese children aged from 8 to 11 years was 262.00 ± 40.57 µ m in the mild myopia group and 236.00 ± 55.08 µ m in the moderate myopia group. The mean SFCT of Chinese children had been reported ranging from 245 ± 66 μ m to 302 ± 63 μ m depending on different age and refractive error range [ 10 12 , 23 ]. The SFCT of the mild myopia group in this research was consistent with a previous study of Chinese children, but SFCT of the moderate myopia group was thinner than that in the study [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other researches concerned of children population found that the thickest locations of choroid were not subfoveal both in myopic and nonmyopic children [ 8 , 20 ]. In the studies of Chinese children, the thickest choroid were located similarly in myopic and nonmyopic participants, either temporal to the fovea [ 10 , 11 , 23 ] or subfoveal [ 12 ], even in the study of relatively large range of refractive error (−11.38 to +8.38 D) [ 10 ]. In this study, the topographic distributions of macular choroidal thickness in mild and moderate myopia children aged 8∼11 years were similar.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies have shown some subtle differences in macular retinal morphology in childhood associated with myopia, with a small magnitude (most studies report an average difference in thickness between myopic and emmetropic children of <10 μm) thinning of the retina in parafoveal and/or perifoveal retinal regions being a typical finding [14,19]. One recent study using long wavelength swept source OCT also examined the impact of myopia upon macular ganglion cell layer (GCL) and retinal nerve fibre layer (NFL) thickness and found myopic children exhibited a significantly thinner perifoveal GCL, but no significant difference in the NFL thickness associated with myopia [19].…”
Section: Introductionmentioning
confidence: 99%